Evaluation of oxidative stress in pseudo-exfoliative glaucoma patients treated with and without topical coenzyme Q10 and vitamin E. Issue 2 (March 2019) - Ozates, Serdar; Elgin, Kadriye Ufuk; Yilmaz, Niyazi Samet; Demirel, Ozlem Ozbas; Sen, Emine; Yilmazbas, Pelin
Purpose: To evaluate the levels of oxidative stress markers such as superoxide dismutase and malondialdehyde in eyes with pseudo-exfoliative glaucoma treated with and without topical coenzyme Q10 (CQ10) and vitamin E (Coqun drop). Methods: This prospective, randomized clinical study was conducted on 64 eyes of 64 patients. All patients underwent phacoemulsification and intraocular lens implantation surgery. Aqueous humor samples were aspirated from the anterior chamber at the beginning of cataract surgery. The pseudo-exfoliative glaucoma + Coqun group received topical Coqun (100 mg CQ10, 500 mg Vitamin E TPGS) twice daily for 1 month preoperatively, while the pseudo-exfoliative glaucoma group consisted of pseudo-exfoliative glaucoma cases who had not taken Coqun. Pseudo-exfoliation syndrome cases formed the pseudo-exfoliation syndrome group. The main outcomes were the superoxide dismutase and malondialdehyde levels of aqueous humor in both groups. Results: The mean aqueous humor superoxide dismutase level was significantly higher in the pseudo-exfoliative glaucoma group than in pseudo-exfoliative glaucoma + Coqun and pseudo-exfoliation syndrome groups (p < 0.001, p = 0.004, respectively). Also, the mean aqueous humor superoxide dismutase level was significantly lower in the pseudo-exfoliation syndrome group than in pseudo-exfoliative glaucoma + Coqun group (p = 0.009). The mean malondialdehyde levels showed no significant difference between the groups (p > 0.05 for all). Conclusion: Our study showed lower aqueous humor level of superoxide dismutase in pseudo-exfoliation syndrome patients compared to pseudo-exfoliative glaucoma patients. Significantly lower superoxide dismutase level was observed in pseudo-exfoliative glaucoma patients who received topical Coqun compared to pseudo-exfoliative glaucoma patients without Coqun treatment. No significant change was observed on the malondialdehyde level during 1-month follow-up period.